2001
DOI: 10.1177/0032885501081001003
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Education for Latina Inmates: The Delimiting Impact of Culture on Prevention Efforts

Abstract: Focus group interviews were conducted with groups of women prisoners to explore inductively their HIV-related needs and concerns. Content analysis determined broad areas of general concern for the women and highlighted obvious cultural distinctions. This article concentrates on those cultural influences as they pertain specifically to Latina women. This population is most at risk of entering the correctional system with HIV infection, and its rates of infection keep rising. Discussions of the concepts of machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This can have serious consequences within the context of traditional relationships. West (2001) noted that many Latinas in her study indicated that departures from traditional sex roles (such as knowledge of sex, or actual or perceived promiscuity) would be considered a lack of respect for their partner, and an affront to his machismo. This includes discussion of safe sex practices.…”
Section: Latino Cultural Values and Attitudes: Impact On Gender Role mentioning
confidence: 99%
See 4 more Smart Citations
“…This can have serious consequences within the context of traditional relationships. West (2001) noted that many Latinas in her study indicated that departures from traditional sex roles (such as knowledge of sex, or actual or perceived promiscuity) would be considered a lack of respect for their partner, and an affront to his machismo. This includes discussion of safe sex practices.…”
Section: Latino Cultural Values and Attitudes: Impact On Gender Role mentioning
confidence: 99%
“…Men, for example, are expected to have considerable sexual knowledge and experience, and may feel the need to prove their masculinity through sexual activity with multiple partners (Marin, 2003; Marin & Gomez, 1998). West (2001) also noted that some Latinos may feel that conceiving children, even outside their primary relationship, enhances their feelings of machismo, and hence they may eschew the use of condoms.…”
Section: Latino Cultural Values and Attitudes: Impact On Gender Role mentioning
confidence: 99%
See 3 more Smart Citations